2011
DOI: 10.1038/nphys2010
|View full text |Cite
|
Sign up to set email alerts
|

The pirouette effect in turbulent flows

Abstract: The disorganized fluctuations of turbulence are crucial in the transport of particles or chemicals 1,2 and could play a decisive role in the formation of rain in clouds 3 , the accretion process in protoplanetary disks 4 , and how animals find their mates or prey 5,6 . These and other examples 7 suggest a yet-to-bedetermined unifying structure of turbulent flows 8,9 . Here, we unveil an important ingredient of turbulence by taking the perspective of an observer who perceives its world with respect to three dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
112
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 29 publications
18
112
2
Order By: Relevance
“…The phenomenon discussed here is illustrated in Fig. 1 A and B, which show the evolution of EðtÞ along the trajectory of a fluid particle in a 3D laboratory water flow (17,18). It illustrates that to build up large kinetic energy requires a longer time than to dissipate the same amount.…”
Section: Significancementioning
confidence: 91%
See 2 more Smart Citations
“…The phenomenon discussed here is illustrated in Fig. 1 A and B, which show the evolution of EðtÞ along the trajectory of a fluid particle in a 3D laboratory water flow (17,18). It illustrates that to build up large kinetic energy requires a longer time than to dissipate the same amount.…”
Section: Significancementioning
confidence: 91%
“…The 3D experiments were performed in a so-called von Kármán mixer, which generates high-Reynolds-number turbulent water flow between two counterrotating disks (15,17). We measured 3D trajectories of tracer particles seeded in the flow using optical Lagrangian particle tracking (17,18). The Reynolds number of the turbulence was in the 350 ≤ R λ ≤ 690 range.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Chakraborty 18 showed that the statistical behaviour of vorticity alignment with local principal strain rates can be significantly different for the corrugated flamelets regime of combustion with Le = 1.0, and for the thin reaction zones regime of combustion with non-unity Lewis number, in comparison to earlier studies. [8][9][10][11][19][20][21][22][23][24][25][26][27][28] For example, in the corrugated flamelets regime, and for the cases with high Karlovitz number and low Le, where the most extensive principal strain rate is controlled by the local dilatation rate, 18 the vorticity vector ⃗ ω predominantly aligns with the intermediate and the most compressive principal strain rates. Such an alignment of the vorticity vector differs from the alignment observed earlier in premixed 11 and non-premixed [8][9][10] flames with unity Lewis number, or in non-reacting flows.…”
Section: Introductionmentioning
confidence: 99%
“…Such an alignment of the vorticity vector differs from the alignment observed earlier in premixed 11 and non-premixed [8][9][10] flames with unity Lewis number, or in non-reacting flows. [19][20][21][22][23][24][25][26][27][28] While each individual species j has its own Lewis number Le j , in simplified models of molecular transport, the Lewis number of the deficient reactant (fuel or oxidant) is often taken to be the characteristic global Lewis number Le 29 as was done in the aforementioned analysis by Chakraborty. 18 It is worth noting here that alternative methods of assigning a characteristic Lewis number have been proposed based on heat release measurements 30,31 and mole fractions of the mixture constituents.…”
Section: Introductionmentioning
confidence: 99%